(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study is the pursuance of useful evaluation index which can estimate the different impression obtained by inhalation of several olfactory stimuli. For this purpose, the principal factors which could determine the impression of olfactory stimulus were attempted to identify. Then the heart rate variability and the cerebral nervous activity were monitored as physiological response. Furthermore the relationship among the factor scores of principal factors and these physiological responses were investigated. As the result, the principal factor of ‘relaxation’ could be estimated accurately with the concentration of the oxy haemoglobin in comparison with index of heart rate variability.